As representações e a verossimilhança das relações interétnicas na obra de Gladstone Osório Mársico (1958-1994) - Rodrigues, Gláucia Elisa Zinani (2024)
The thesis analyzes interethnic representations and verisimilitude in the literary works of the writer from Rio Grande do Sul, Gladstone Osório Mársico (1927–1976). This research defends the hypothesis that social and local verisimilitude, particularly in the context of the Erechim colony, constitutes a central element in the representation of interethnic relations in his satiricalparodic production. The general objective is to contextualize the interactions between Indigenous peoples, natives, and immigrants depicted in Mársico’s works, assessing whether these interactions effectively occurred and how they were literarily constructed. The specific objectives include: developing a theoretical-critical biography of the writer, focusing on their participation in the historical context of Erechim/RS; analyzing the structure of their work, with an emphasis on the representation of rural and urban spaces; and investigating interethnic relations throughout their production by comparing their literary texts. The study’s corpus encompasses the entirety of Mársico’s literary production, published between 1958 and 1994, including the works My Death and Other Lives (1958), followed by Cats in Plainclothes (1962), Autumn Mushrooms (1972), Turtle (or the story of a municipality at a step by) (1974), and concluding with the posthumous publication of Foruncule (1994). These works reflect the social and cultural dynamics of the northern region of Rio Grande do Sul, where Mársico resided for many years. The justification for this study lies in the relevance of Mársico's works, which, by portraying historical events and figures from Erechim/RS with irony and social critique, offer a unique representation of interethnic relations and local history. His production combines historical and satirical elements, addressing prejudices, cultural differences, and social tensions while encouraging readers to reflect through parodic humor. Methodologically, the study dialogues with Cultural History and situates itself at the interface between Literature and History, with particular attention to the concept of ethnicity developed by Fredrik Barth. Through the representation of interethnic relations, the analysis focuses on four main categories: 1) the interaction between Indigenous peoples and nationals, emphasizing the struggle for land; 2) representations within spaces of sociability; 3) the representation of women in interethnic relations, focusing on interethnic marriages; and 4) interethnic relations under the influence of Nazi and Fascist ideologies. By analyzing interethnic relations, Mársico's personal experiences, and the sociocultural context of his time, the dissertation highlights the significance of his work as both a literary and historical document. His writing provides a critical and multifaceted view of individuals, roles, and social spaces in Erechim/RS, with satirical humor serving as a tool for reflection and questioning.